AIAA SCITECH 2023 Forum 2023
DOI: 10.2514/6.2023-1555
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Approach towards Fuselage Optimization for Effective Boundary Layer Ingestion

Abstract: Optimization studies for improved fuselage designs primarily focus on drag reduction. However, when considering an alternative configuration where the stability requirements are assumed to be fulfilled by the main wing, eliminating the need for a tailplane, the fuselage design requirements are reconsidered. This work considers not only the reduction of drag but ensuring a component of lift as well as considering energy recovery potential for propulsion integration. The numerical modelling approach (turbulence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…The mesh construction was similar to the 3D axisymmetric transonic validation study (Odendaal et al , 2023). The domain size for the study indicated a distance of 6 body lengths behind the body was sufficient to capture the drag coefficient with less than one 1% difference.…”
Section: Mesh Constructionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mesh construction was similar to the 3D axisymmetric transonic validation study (Odendaal et al , 2023). The domain size for the study indicated a distance of 6 body lengths behind the body was sufficient to capture the drag coefficient with less than one 1% difference.…”
Section: Mesh Constructionmentioning
confidence: 99%
“…The multi-objective trade-off optimisation algorithm SHERPA was used based on its capability to make large geometrical changes, which constantly refines each parameter input range to provide multiple optimum geometries. All the models selected were based on the comparative studies and validation completed in Odendaal et al (2023). The simulations were completed on a single personal computer with 16-cores and took approximately 65 days to complete the optimisations.…”
Section: Boundary Conditions Turbulence Transition and Optimisation M...mentioning
confidence: 99%
See 2 more Smart Citations